ANALISIS PENGARUH LETAK DAN TOPOGRAFI PLOT MAIN NURSEY TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DENGAN SISTEM FERTIGASI TETES (DRIP FERTIGATION SYSTEM) - Setiyawan, Achmad Fauzi Garin; Andayani, Neny; Noviana, Githa (Agro Estate, 2023)
Oil palm productivity cannot be separated from where the seeds come from. The success of a nursery is seen from the quality of the seeds produced. One factor that influences seed growth is the fertigation system. One of the renewable fertigation systems is the drip fertigation system. This research aims to analyze the comparison of vegetative growth in various plot conditions in the drip fertigation system by actually comparing the results of measuring the vegetative growth of seedlings with the drip fertigation system. The research was carried out at PT. Bumi Permai Lestari Perkebunan Bukit Intan Estate (BINE) is located in Ds.Terentang, Kec.Kelapa, West Bangka Regency, Bangka Belitung Province. This research was carried out from April 2023 to October 2023. The research was carried out using quantitative analysis methods as primary data for the research data which was analyzed using the one-way variance test method at a 5% level followed by DMRT test. The results showed that plots with flat elevations and normal distances had superior vegetative growth compared to seedlings in plots located far from reservoirs and plots with sloping elevations. It was concluded that the location and topography of the main nursery plot had a real (significant) influence on the vegetative growth (seedling height, number of leaves, and stem circumference) of oil palm seedlings with a drip fertigation system, where the sloping topography had an unfavorable influence on the growth of oil palm seedlings.